"INSYA ALLAH" VERSI ARAB, INDONESIA, DAN INGGRIS: SEBUAH KAJIAN PENERJEMAHAN SYAIR LAGU - Mulawarman (Jurnal Penerjemahan, 2014)
Lyrics to a song serve not only as a complement but also constitute an important part to determine the theme and mission of a song. Lyrics can stir up emotions of happiness, sadness, and enthusiasm to those who listen to the song. Thus, translating the lyrics of a song should take into account these elements in addition to its aesthetic element. For that reason, this paper discusses the translation of the lyrics of the song 'Insya Allah' into Indonesian and English (TT/Target Text) from theArabic version (ST/Source Text) in order to acquire a level of "equivalence" for translating the ST into TT. The results show that the translation of the song's lyrics into Indonesian and English are able to convey the meaning and message of the lyrics from Arabic, although its rendition has not yet captured perfectly the aesthetic element.